Regulation of Satellite Cell Homeostasis by C/EBPβ: Therapeutic Perspectives - Lala-Tabbert, Neena (Université d'Ottawa / University of Ottawa, 2016)
Regeneration of adult skeletal muscle relies upon a population of quiescent myogenic progenitor cells, called satellite cells (SCs). Upon injury, SCs activate, proliferate, differentiate and fuse to make new myofibers or to repair damaged ones. SCs can also self-renew to repopulate the SC niche. The balance between differentiation and self-renewal is critical to maintain muscle homeostasis and changes in this equilibrium can lead to chronic muscle degeneration. For example, Duchenne’s muscular dystrophy (DMD) is characterized by rounds of muscle degeneration and regeneration leading to increased muscle wasting. One approach to treat DMD is transplantation of SCs. For this treatment to be viable, transplanted cells must contribute to repairing injured muscle and repopulating the SC niche. Here, we show that the transcription factor CCAAT/Enhancer Binding Protein beta (C/EBPβ) regulates SC function. C/EBPβ is down-regulated during differentiation and persistent expression of C/EBPβ inhibits differentiation and expression of the myogenic regulatory factors MyoD and Myogenin. C/EBPβ also promotes Pax7 expression by directly binding to and regulating Pax7 transcription. Using genetic tools to conditionally excise C/EBPβ expression in SCs, we found that C/EBPβ-null SCs lose quiescence and precociously differentiate at the expense of self-renewal. After a single injury, C/EBPβ-deficient SCs failed to self-renew, resulting in impaired muscle repair after a second injury. C/EBPβ-induced quiescence also requires upregulation of caveolin-1. Furthermore, pharmacological manipulation of C/EBPβ expression with the phosphodiesterase inhibitor, isobutylmethylxanthine (IBMX), increased the number of cells available for transplantation into dystrophic muscle and enhanced the expression of stem cell markers in a C/EBPβ-dependent fashion. IBMX treatment improved cell survival and migration, engraftment into the SC niche and repair of dystrophic muscle. Together, these results demonstrate that C/EBPβ is an important regulator of SC function and that pharmacological manipulation of C/EBPβ improves culture conditions for the expansion and selection of SCs available for cell therapy for the treatment of muscular dystrophies.
Keywords: C/EBPβ; Satellite Cells; Self-Renewal; Differentiation; Quiescence; Duchenne's Muscular Dystrophy; IBMX; Transplantation